2020
DOI: 10.1111/crj.13217
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of immune‐inflammation indices in metabolic response and outcome after curative radiotherapy in patients with non‐small cell lung cancer

Abstract: Introduction Role of systemic inflammation response in prognosis of several solid tumors has been evaluated in quite a lot of recent reports. Objectives In this study, we aimed to investigate the effect of a novel immune response marker; systemic immune‐inflammation index (SII) on metabolic response to chemoradiotherapy and outcome in patients with non‐small cell lung cancer (NSCLC). Other several inflammatory indices such as neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), lymphocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…Several inflammation and immunity-based indicators, including lymphocyte count, neutrophil-lymphocyte ratio (NLR), and platelet-lymphocyte ratio (PLR), have been used in predicting survival outcomes (8)(9)(10)(11). Systemic immune-inflammation index (SII), calculated by lymphocyte, neutrophil, and platelet counts, reflects the balance of host inflammatory and immune status and is an established prognostic factor in several malignies (12)(13)(14). However, the prognostic value of SII in breast cancer patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several inflammation and immunity-based indicators, including lymphocyte count, neutrophil-lymphocyte ratio (NLR), and platelet-lymphocyte ratio (PLR), have been used in predicting survival outcomes (8)(9)(10)(11). Systemic immune-inflammation index (SII), calculated by lymphocyte, neutrophil, and platelet counts, reflects the balance of host inflammatory and immune status and is an established prognostic factor in several malignies (12)(13)(14). However, the prognostic value of SII in breast cancer patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In the peripheral blood of patients who develop different types of cancers, the numbers of neutrophils and platelets increase remarkably, and these cells produce inflammatory cytokines and chemokines, which may contribute directly to malignant progression [ 25 27 ]. Although lymphocytes in tumors may not always be active due to immune escape or tolerance, increased infiltration is associated with a better prognosis in cancer patients [ 28 ]. Therefore, it is concluded that inflammation plays a crucial role in the development and progression of tumors, and SII may be a reliable prognostic index for the survival of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since most of the studies usually lean on surgery and/or chemotherapy as treatment modalities, we focused our attention in the literature on the studies on patients who were subjected to radiotherapy, as our aim is to make a comparison with the results of our study. All series had a retrospective design and included patients with locally advanced NSCLC treated with curative radiotherapy 1,23–28 . The inferences obtained can be listed as follows: First, these indices were often examined individually in published studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are also studies examining the combinations of two, triple and sometimes four indices with different cut‐off values. Yet, significant results were obtained for one or two indices, whereas some studies failed to show a noteworthy relationship 23,25,26 . Second, some researchers evaluated post treatment values and changes regarding these indices.…”
Section: Discussionmentioning
confidence: 99%